Diallyl trisulfide inhibited tobacco smoke-mediated bladder EMT and cancer stem cell marker expression via the NF-κB pathway in vivo. Issue 3 (March 2021) - Geng, Hao; Guo, Wenhao; Feng, Lei; Xie, Dongdong; Bi, Liangkuan; Wang, Yi; Zhang, Tao; Liang, Zhaofeng; Yu, Dexin
Objective: This study examined the effect of the NF-κB pathway on tobacco smoke-elicited bladder epithelial–mesenchymal transition (EMT) and cancer stem cell (CSC) marker expression in vivo . The effect of diallyl trisulfide (DATS) treatment was also examined. Methods: BALB/c mice were exposed to tobacco smoke and treated with an NF-κB inhibitor and DATS. Western blotting, quantitative real-time PCR, and immunohistochemical staining were used to detect the changes of relevant indices. Results: Phosphorylated inhibitor of kappa-B kinase alpha/beta expression and p65 and p50 nuclear transcription were increased by tobacco smoke exposure, whereas inhibitor of kappa-B expression was decreased. In addition, tobacco smoke reduced the expression of epithelial markers but increased that of mesenchymal and CSC markers. Our study further demonstrated that tobacco smoke-mediated EMT and CSC marker expression were attenuated by inhibition of the NF-κB pathway. Moreover, DATS reversed tobacco smoke-induced NF-κB pathway activation, EMT, and the acquisition of CSC properties in bladder tissues. Conclusions: These data suggested that the NF-κB pathway regulated tobacco smoke-induced bladder EMT, CSC marker expression, and the protective effects of DATS.